2013
DOI: 10.1097/jan.0b013e318282751e
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Interdisciplinary Collaboration in Addictions Education and Training

Abstract: Developing a workforce of multidisciplinary healthcare professionals equipped with the knowledge and skills to collaboratively address the public health crisis of alcohol and other drug (AOD) use is critical for effectively identifying, preventing, and managing AOD conditions and their sequelae. Despite general enthusiasm for interdisciplinary education and training, little is known overall about the nature and outcomes of interdisciplinary collaboration in addictions education and training. We conducted a fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…We used a scoping study, a rigorous and comprehensive method [ 14 ], to identify and describe literature about mobile NSPs and specifically to answer this question: what is known about the design, operational characteristics, and services offered, client characteristics, service utilization, and impact of mobile NSPs? This method allowed for a broad charting of literature without narrow restrictions (e.g., specific populations, specific types of study designs, and/or highly specific definitions of methodological rigor) that might reduce what can be learned from existing literature [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We used a scoping study, a rigorous and comprehensive method [ 14 ], to identify and describe literature about mobile NSPs and specifically to answer this question: what is known about the design, operational characteristics, and services offered, client characteristics, service utilization, and impact of mobile NSPs? This method allowed for a broad charting of literature without narrow restrictions (e.g., specific populations, specific types of study designs, and/or highly specific definitions of methodological rigor) that might reduce what can be learned from existing literature [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The separation between primary health care and mental health care creates barriers to mental health care, which can be eliminated by the employment of a collaborative care model (American Psychological Association, Presidential Task Force on Integrated Health Care For An Aging Population, 2008; Gunn & Blount, 2009; Raue, McGovern, Kiosses, & Sirey, 2017; Substance Abuse and Mental Health Services Administration and Health Resources and Services Administration, 2016). Research demonstrates that interdisciplinary patient care teams produce better clinical outcomes and higher patient satisfaction (Broyles, Conley, Harding, & Gordon, 2013; Müller et al, 2015; Reiss-Brennan et al, 2016; Theodoridou et al, 2015). The Patient-Centered Primary Care Collaborative (PCPCC) found that Blue Cross/Blue Shield’s statewide integrative primary care efforts in Michigan produced a 15% decrease in adult Emergency Department visits, and a 21% decrease in adult ambulatory care sensitive inpatient stays, with consequent significant cost savings to the health care system (PCPCC, 2017).…”
mentioning
confidence: 99%
“…Thus, interdisciplinary collaboration becomes imperative to ensure convergence and synergy of efforts to attain a common treatment outcome. This tactic was found to be favored by professionals as it allows for shared learning and understanding 23 , and is deemed to be appropriate in addressing the complexity of substance abuse and/or the needs of clients. 24,25 Aside from a theoretical and empirical underpinning, a multidisciplinary approach to treatment has also been identified by the United Nations Office on Drugs and Crime (UNODC) and the World Health Organization (WHO) as an important component of a comprehensive treatment system 26 , and is a key principle of the national-level policy on drug rehabilitation.…”
Section: Discussionmentioning
confidence: 99%